Hubungan Antara Nilai Leukosit, Rasio Jumlah Neutrofil-limfosit (NLR), C-Reactive Protein (CRP) dan Prokalsitonin dengan Skor Pediatric Logistic Organ Dysfunction (PELOD-2) sebagai Prediktor Derajat Keparahan Penyakit pada Anak Sakit Kritis - Rismala Dewi; Risa Imanillah (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: Children admitted to the Pediatric Intensive Care Unit (PICU) are a vulnerable population with a high degree of morbidity and mortality. Laboratory tests such as full blood count and infection parameters were additional tests that help clinicians assess the severity of pediatric patients’ illnesses. Besides that, the PELOD-2 score, a scoring system, also helped evaluate the degree of a critical condition in children. However, the components of PELOD-2 are quite complicated and unattainable in the limited-resource healthcare facilities. We expect that the simple laboratory examinations could be an alternative to the PELOD-2 score when the score is not accessible. This study evaluates the correlation between leukocyte count, Neutrophil-Lymphocyte Ratio, CRP, and PELOD-2 score. Methods: This is a comparative retrospective study in 75 pediatric patients admitted in PICU RSCM from January 2019 to August 2020 and passed the ethical review. The exclusion criteria for this research was a patient with incomplete data. To analyze the variables independently, we used Spearman analysis. Meanwhile, to evaluate the relationship between the independent variables and PELOD-2 simultaneously, we used logistic regression. Results: Based on the Spearman analysis, this study found a significant correlation between Leukocyte count (0,059; CI:90%) and PELOD-2 score, as well as Procalcitonin (0,076; CI: 90%) and PELOD-2. The logistic regression also showed that Leukocyte count and Procalcitonin significantly correlated with the PELOD-2 score.Conclusion: Leukocyte count and Procalcitonin can be an alternative to the PELOD-2 score when healthcare facilities cannot fulfil the PELOD-2 scoring system’s components.